(untitled) (Faridpur Medical College Journal, 2019)
Gastrointestinal Stromal Tumours (GISTs) are a rare group of mesenchymal tumour arising in gastrointestinal tract. The clinicopathological features are variable and surgical resection with chemotherapy is the main modality of treatment. We retrospectively analyzed 20 different types of GIST patients over a period of 9 years to understand clinical presentation, pathological features, treatment and survival. The tumour was most commonly seen in the patients (75%) of age range of 30-60 years. Twelve (60%) were male and 8 (40%) were female patient. Forty percent of the tumours were located in the stomach followed by small intestine (35%) and omentum (20%). Abdominal mass (70%), abdominal pain (45%) and GIT bleeding were the common clinical presentation. The size of the tumours ranged from 3 to 22 cm. All patients of our series underwent surgical excision of tumour. NIH risk categorization showed 15 (75%) patients belong to low risk category, 2(10%) patients were of intermediate risk group and 3 (15%) were of high risk group. Out of 20 cases CD117 positivity was seen in 17 (85%) cases offered adjuvant Imatinib mesylate. No patient in our series offered neo adjuvant chemotherapy. Postoperative follow up was done 6 monthly. GIST’s are most common non epithelial tumour of the GIT. It is common in 4th and 5th decades. Abdominal mass and abdominal bleeding are the most common clinical presentation. Stomach is the most common site. Surgical resection is the best modality of treatment. Imatinib mesylate is used for adjuvant therapy. Regular follow up helps in diagnosing disease recurrence. Faridpur Med. Coll. J. Jul 2018;13(2): 66-69